Exploring antioxidant potential of thiazole derivatives through functional group engineering: a molecular docking and molecular dynamics approach - Haura Habiba; Hendrik Manullang; Putri Sekar Kristiany; Zahra Wahdini; Yuni Marhayuni; Citra Deliana Dewi Sundari; Atthar Luqman Ivansyah; Endang Rahmat; Refsya Azanti Putri; Sarmoko; Muhammad Yogi Saputra (Pharmacy Reports, 2026)
Thiazole derivatives are promising antioxidant candidates due to their tunable structures and diverse biological activities. This study investigated the effect of functional group engineering on the antioxidant potential of thiazole derivatives using molecular docking and 100 ns molecular dynamics simulations against the antioxidant-related target protein 1U7F. Five substituents, namely amide, hydroxyl, catechol, imidazole, and thiol groups, were introduced into the thiazole scaffold. Docking results showed that the amide-substituted derivative exhibited the strongest binding affinity, with a binding energy of −186.364 kJ/mol, followed by catechol, hydroxyl, imidazole, and thiol derivatives. Interaction analysis indicated that amide and hydroxyl-containing ligands formed more extensive hydrogen-bonding interactions with key active-site residues, contributing to stronger protein–ligand stabilization. Molecular dynamics analyses based on RMSD, RMSF, radius of gyration, solvent-accessible surface area, and hydrogen bonding confirmed that all complexes remained structurally stable throughout the simulation. The thiol-substituted derivative showed the highest dynamic structural stability, whereas MM-PBSA analysis revealed that the amide-substituted derivative had the most favorable binding free energy. Overall, these findings demonstrate that functional group modification significantly influences the binding affinity and dynamic stability of thiazole derivatives. The amide group is the most promising substituent for enhancing antioxidant potential through stronger protein binding, while the thiol group contributes to superior structural stability during simulation.